The his and hers of sharing : a qualitative research on the division of household labour among dual-earner couples in Singapore. - Tay, Adelle Siew Min. (2011)
Despite changing attitudes towards female participation in the paid labour market, working women in the twenty-first century still face a similar paradox as those twenty years ago – the double bind between work and family life. While many researchers have focused on the division of household labour in dual-career households, few have looked at the sort of meanings husbands and wives place on doing housework – i.e. the way in which domestic tasks are constructed, understood, and perceived – and how these are linked to the culture and society in which these individuals are situated. Thus, this research paper looks at middle-class Singaporeans’ views on the division of household labour and how they employ gender ideologies and make use of culture to give meaning to housework.